Implementasi Standar Sumber Daya Manusia dan Pelayanan Minimal Kesehatan di Kota Pekalongan - Anik Indriono (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
Hospital is a health service facility that must provide services according to applicable service standards. One of the front guards of a hospital is an Emergency Room (IGD) which will provide emergency assistance to every patient. Emergency is a condition that threatens life and disability, so it needs fast, precise, effective and quality action. This can be achieved if the hospital has a standard of service in the Emergency Room. This study aims to determine the implementation of HR standards and minimal services in hospital emergency departments. This research is a qualitative research with a sociological juridical approach. Sociological juridical is legal research that uses secondary data as initial data, which is then followed by primary data or field data. The juridical aspect in this research is the regulation of the minister of health regarding the standards of the Hospital Emergency Room and the sociological aspect is the implementation of the rules in the ministerial decree by the hospital. Sources of legal materials for this research include primary and secondary legal materials. Data collection techniques used are through interviews and literature. The results showed that the Standard Emergency Room is regulated in Law No. 44 of 2009 concerning the Hospital. In particular, the IGD standard has been regulated in the Republic of Indonesia's Minister of Health Kepmenkes No.856 / Menkes / SK / IX / 2009 regarding the standard of Hospital Emergency Room Installation. But in reality in the field, the hospital has not fully implemented these regulations, so the quality of service in the ER is less. Thus the patient's right to get quality services is neglected. According to the Hospital Law Article 29 Paragraph 1 point (a) that "Hospitals are obliged to provide safe, quality, anti-discrimination, and effective health services by prioritizing the interests of patients in accordance with Hospital service standards". The supporting factors for implementation are high human resource motivation and the inhibiting factors, namely the opportunity and cost of further study for nurses, do not yet exist.Keywords:Implementation; Human Resource Standards; Minimum Service Standars; Hospital.